2022
DOI: 10.3390/bioengineering9120777
|View full text |Cite
|
Sign up to set email alerts
|

A High-Accuracy Detection System: Based on Transfer Learning for Apical Lesions on Periapical Radiograph

Abstract: Apical Lesions, one of the most common oral diseases, can be effectively detected in daily dental examinations by a periapical radiograph (PA). In the current popular endodontic treatment, most dentists spend a lot of time manually marking the lesion area. In order to reduce the burden on dentists, this paper proposes a convolutional neural network (CNN)-based regional analysis model for spical lesions for periapical radiographs. In this study, the database was provided by dentists with more than three years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…This research tested the segmentation method proposed in previous research [27]. The result showed that it worked well for front teeth but had difficulty with back teeth due to lighting or imaging conditions.…”
Section: Image Segmentationmentioning
confidence: 96%
See 1 more Smart Citation
“…This research tested the segmentation method proposed in previous research [27]. The result showed that it worked well for front teeth but had difficulty with back teeth due to lighting or imaging conditions.…”
Section: Image Segmentationmentioning
confidence: 96%
“…The accuracy of this step affected the determination of the target object in the later steps. This research tested the fixed threshold using the Otsu algorithm, as mentioned in [25]; the iterative algorithm, as mentioned in [26]; and the adaptive threshold, as mentioned in [27]. However, for the molars' PA, the pixel brightness was a significant factor, which is different from the PA of a single tooth.…”
Section: Adaptive Thresholdmentioning
confidence: 99%
“…The improvement in efficiency and quality provides clinicians more time for patient care. Furthermore, periapical (PA) image is utilized as an adjunct diagnostic tool, particularly in the assessment of conditions such as apical lesions [10], implants [11], and furcation involvement [12]. DPR images refer to extraoral radiographs [13], typically encompassing all teeth alongside adjacent skeletal structures and nerves, providing two-dimensional information about dental and maxillofacial osseous anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…Filters have been helpful in reducing the impact of point creation on cutting technology and recognition in PA [ 17 ]. Furthermore, adaptive thresholds have been suggested to improve the application of cropping technology in dental radiology research [ 18 ]. Regarding the identification of disease symptoms, the backpropagation neural network has been used to diagnose dental caries with an accuracy rate of 94.1% [ 19 ].…”
Section: Introductionmentioning
confidence: 99%